Liver X receptor β controls thyroid hormone feedback in the brain and regulates browning of subcutaneous white adipose tissue - Miao, Yifei (Proc Natl Acad Sci U S A, 2015)
The recent discovery of browning of white adipose tissue (WAT) has raised great research interest because of its significant potential in counteracting obesity and type 2 diabetes. Browning is the result of the induction in WAT of a newly discovered type of adipocyte, the beige cell. When mice are exposed to cold or several kinds of hormones or treatments with chemicals, specific depots of WAT undergo a browning process, characterized by highly activated mitochondria and increased heat production and energy expenditure. However, the mechanisms underlying browning are still poorly understood. Liver X receptors (LXRs) are one class of nuclear receptors, which play a vital role in regulating cholesterol, triglyceride, and glucose metabolism. Following our previous finding that LXRs serve as repressors of uncoupling protein-1 (UCP1) in classic brown adipose tissue in female mice, we found that LXRs, especially LXRβ, also repress the browning process of subcutaneous adipose tissue (SAT) in male rodents fed a normal diet. Depletion of LXRs activated thyroid-stimulating hormone (TSH)-releasing hormone (TRH)-positive neurons in the paraventricular nucleus area of the hypothalamus and thus stimulated secretion of TSH from the pituitary. Consequently, production of thyroid hormones in the thyroid gland and circulating thyroid hormone level were increased. Moreover, the activity of thyroid signaling in SAT was markedly increased. Together, our findings have uncovered the basis of increased energy expenditure in male LXR knockout mice and provided support for targeting LXRs in treatment of obesity.